2020
DOI: 10.46827/ejoe.v5i2.3476
|View full text |Cite
|
Sign up to set email alerts
|

Towards E-Learning in Basic Schools During Covid-19: Insights From Ghanaian Teachers

Abstract: In the wake of the current closure of schools in Ghana, basic schools have been tasked to deliver teaching and learning using e-learning. This study seeks to explore the readiness of teachers in Ghanaian basic schools to undertake e-learning. Using an online questionnaire, data was collected from 108 teachers in both private and public basic schools in Ghana. A factor analysis was conducted to identify the challenges that influenced the ability of basic school teachers to teach using e-learning. The study find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Moreover, Scherer et al (2021) found an insignificant relationship between self-belief with institutional support and teaching presence perception. Nevertheless, scholars commonly demonstrate positive effects of psychological factors, such as attitude, behaviour, acceptance and motivation (Aguilerahermida, 2020; Allam et al, 2020;Brusilovsky, 2020;Dahleez et al, 2021b;Mohamed et al, 2021), and other technology-based factors, such as digital tools, facilities and infrastructural preparedness (Amanor-mfoafo et al, 2020;Gani et al, 2022;Haider and Al-Salman, 2020;Rapanta et al, 2020).…”
Section: Challenges Facing the Efficacy Of Deployed E-learning Systemsmentioning
confidence: 99%
“…Moreover, Scherer et al (2021) found an insignificant relationship between self-belief with institutional support and teaching presence perception. Nevertheless, scholars commonly demonstrate positive effects of psychological factors, such as attitude, behaviour, acceptance and motivation (Aguilerahermida, 2020; Allam et al, 2020;Brusilovsky, 2020;Dahleez et al, 2021b;Mohamed et al, 2021), and other technology-based factors, such as digital tools, facilities and infrastructural preparedness (Amanor-mfoafo et al, 2020;Gani et al, 2022;Haider and Al-Salman, 2020;Rapanta et al, 2020).…”
Section: Challenges Facing the Efficacy Of Deployed E-learning Systemsmentioning
confidence: 99%
“…Global education has over many years exploited advances in information and communication technology to plan for a staged transition from traditional models to e-learning. In developed economies, e-learning has become an alternative but key channel of instructional delivery in Learner satisfaction in higher education higher education institutions (Amanor et al, 2020;Mohan et al, 2022). Several studies indicate the effectiveness of e-learning that culminate in learner satisfaction.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Literature reviews suggest that learner-facilitator interactions are critical to better student grades, higher student satisfaction and students' higher-order cognition (Elfeky, 2018). Electronic learning is still in its infancy in developing economies which experience challenges unique to third world countries (Kotouaa et al, 2015;Amanor et al, 2020). Studies need to be conducted to find out if the learner-facilitator interactions have a positive effect on learner satisfaction and are substitutable.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In developing countries such as Ghana, OL is new to the education system, which largely depends on face-to-face teaching and learning. Indeed, the education system lacks basic facilities such as computers, Internet access, and accessible platforms for providing OL services to students (Amanor-mfoafo et al, 2020). This raises critical questions as to whether teachers are (being) prepared to embrace the new OL system to support the teaching and learning of all students in the classroom.…”
Section: Introductionmentioning
confidence: 99%